The Constraints in Shariah-Compliant Asset-Backed Securities Issuance at Islamic Banking Industries in Indonesia - Supyadillah, Asep; Maulana, Muhammad Al-Fayyadh; Fisabilillah Miswin, Nur Ilhamillaili (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
Abstract. The paper examines the responses of Islamic bank executives in Indonesia on constraints precluding the Sharia-compliant Asset-backed Securities (SABS) issuance, especially from sharia and legal perspectives. This research uses socio-legal and inductive approaches, analyzed with content analysis. The research f inds that, first, despite its necessity, the SABS concept brings risks and constraints in its implementation. Second, the constraints to SABS issuance include the difficulties in procuring assets. Third, the constraints in the legal aspect include the basis of bank authority to sell assets to SABS issuers, the types of assets, the transfer process to special purpose vehicles (SPV), the dubiety in the clauses managing bankruptcy remoteness and perfection of security interest, and the problems of accounting, asset bookkeeping, and taxation.Abstrak. Artikel ini menganalisis respon pelaku industry bank syariah di Indonesia terhadap kendala pada penerbitan Efek Beragun Aset Syariah (EBAS), dari perspektif syariah dan hukum. Penelitian ini menggunakan pendekatan sosio-hukum dan induktif, dengan analisis konten. Penelitian menemukan, pertama, sekalipun secara konsep dibutuhkan dan bermanfaat, EBAS berhadapan dengan potensi risiko dan hambatan dalam implementasinya. Kedua, kendala penerbitan EBAS antara lain kesulitan pengadaan aset. Ketiga, kendala aspek hukum meliputi dasar kewenangan bank untuk menjual aset kepada penerbit EBAS, jenis aset yang menjadi dasar penerbitan EBAS, proses pengalihan aset ke Special Purpose Vehicle (SPV), ketidak jelasan ketentuan bankcruptcy remoteness and perfection of security interest, serta masalah akuntansi, pencatatan aset, dan perpajakan.